A Localization Algorithm Based on NLOS Identification with Improved VB-AKF. Issue 1 (April 2020) - Chu, Hao; Fan, Zhibo; Wang, Fei; Ji, Peng; Wu, Chengdong
Abstract: As a research hotspot, wireless sensor network (WSN) has a wide range of application prospect. The non-line of sight (NLOS) localization is one of the most basic techniques. In order to mitigate the NLOS influence and increase the localization accuracy, we proposes an improved VB-AKF algorithm in this paper. Firstly, the propagation state of the signal is identified. Then, for the LOS and NLOS mix environments, we reduce the NLOS error by changing the attenuation coefficient. And the maximum likelihood (ML) method is used for localization. Finally, the simulation results show that our method can effectively obtain higher localization accuracy.